A New THz Frequency Band Generation for Optical radio System of RFID Applications - B. Sansoda; S. Thongmee; N. Pornsuwancharoen; P.P. Yupapin; R. Phromloungsri (My University, 2012)
We propose a novel system that can be used to generate the new optical communication that have shown the optimize results with various RFID applications. Gaussian pulse with center wavelengths from 1,300 nm are used, which this system is very simple for used. Whereas the suitable simulation parameters are input power, pulse width, ring radii are 5-12 μm and the material refractive indices (κ) are 0.10-0.97. The potential applications carrier generation for a new THz RFID is 0.2 THz by micro-nano ring resonator device.
Keywords: Photonic and Optical Devices